Anthropos Metron versus Bous Metron? The Significance and Suffering of Animals in Regard to Sacrificial Rituals - Perliński, Dominik (ETHICS IN PROGRESS, 2022)
Humanity has practised animal sacrifice for the greater part of its history, from the time of the Neolithic Revolution. The ritual forms have varied, depending on the culture. They have also been subject to change, in connection with the development of human understanding and knowledge of animals, which is reflected in the ontological, cultural and moral status assigned to animals in the human world. Sacrificing animals involved not only killing them in a particular way – their treatment was sometimes sophisticated or ‘ritualistic’; often it was simply cruel. Human attitudes towards non-human living beings have also evolved in the context of animal killing and sacrifice. The treatment of animals reveals a great deal about human beings – in terms of their culture, beliefs, and morals. The article outlines this issue in a historical manner, referring to the practices adopted in selected cultural circles (in the Mediterranean Basin): ancient Mesopotamia and Greece, as well as in Judaism and Islam. The key findings of researchers are presented, along with the evaluations of philosophers, ethicists and anthropologists.